Novel Genetic Findings in a Chinese Family with Axenfeld-Rieger Syndrome - Kuanshu Li; Liu Yang; Ying Liu; Ding Lin (Journal of Ophthalmology)
Purpose. To describe a Chinese family with Axenfeld-Rieger syndrome (ARS) and report our novel genetic findings. Methods. Nine members of the same family underwent complete ophthalmologic examinations and genetic analysis. Genomic DNA was isolated from veinal blood and amplifed using PCR; the products of PCR were sequenced and compared with FOXC1 and PITX2 genes, from which the mutations were found. Results. Through the ophthalmologic examinations, 8 subjects were diagnosed as ARS and 1 subject was normal. A homozygous mutation c.1139_1141dupGCG(p.Gly380_Ala381insGly) and a heterozygous mutation c.1359_1361dupCGG(p.Gly456_Gln457insGly) in FOXC1 were identified in all subjects. The mutation (c.-10-30T>C) was identified in PITX2 in subjects III-1 and III-3. Conclusions. We found novel gene mutations in a Chinese family with ARS, which provides us with a better understanding of the gene mutation spectrum of ARS and the assistance for the genetic counseling and gene-specific therapy in the future.